EDUKASI JAMU DALAM MENGATASI MASALAH IMUNITAS TUBUH - Elok Ramdhany Putri; Bagus Dwi Cahyono; Irwanto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
: Health problems are classic problems that still often occur, especially during a pandemic. The problem in terms of health in Sumber Gresik Hamlet is quite severe which is due to the lack of public health awareness. There are still people who live with unhealthy lifestyle habits. The purpose of this service activity is to provide ideas for community empowerment with alternative solutions in the form of education on household herbal medicine management. The method used is outreach to the community and poster distribution. In this service activity, the researchers collaborated with the youth groups of Dusun Sumber Gresik as a place for counseling on herbal medicine processing. The results of community service are increasing the motivation of villagers and changing their mindset about being more aware of caring for health and the environment.